2007
DOI: 10.1104/pp.107.097154
|View full text |Cite
|
Sign up to set email alerts
|

Cowpea Chloroplastic ATP Synthase Is the Source of Multiple Plant Defense Elicitors during Insect Herbivory  

Abstract: In cowpea (Vigna unguiculata), fall armyworm (Spodoptera frugiperda) herbivory and oral secretions (OS) elicit phytohormone production and volatile emission due to inceptin [Vu-In; 1 ICDINGVCVDA 2 ], a peptide derived from chloroplastic ATP synthase g-subunit (cATPC) proteins. Elicitor-induced plant volatiles can function as attractants for natural enemies of insect herbivores. We hypothesized that inceptins are gut proteolysis products and that larval OS should contain a mixture of related peptides. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
94
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(102 citation statements)
references
References 83 publications
8
94
0
Order By: Relevance
“…In summary, we interpret the phylogenically idiosyncratic nature of elicitor action as additional indirect evidence for the existence of volicitin and inceptin receptors in maize and cowpea, respectively, and although little is known about caeliferins, modern tools for genetic mapping, microarray, and mutant analyses will expedite future discoveries (11,18,35,44).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In summary, we interpret the phylogenically idiosyncratic nature of elicitor action as additional indirect evidence for the existence of volicitin and inceptin receptors in maize and cowpea, respectively, and although little is known about caeliferins, modern tools for genetic mapping, microarray, and mutant analyses will expedite future discoveries (11,18,35,44).…”
Section: Discussionmentioning
confidence: 88%
“…Likewise, the inactivity of FACs in A. thaliana, cowpea, and tomato argues against relatively non-specific pore-formation mechanisms and supports plant recognition mediated by specific binding proteins (39,41). ln contrast to FACs, inceptin represents a seemingly uncommon divergence from direct plant recognition of an insect-synthesized elicitor to an indirect recognition system based on insect catabolism (14,18,53).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The chemical nature of a few elicitors of feeding-induced plant defense responses are known: fatty acid-amino acid conjugates, including volicitin, of several lepidopterans (6,7,(23)(24)(25)(26); peptides derived by proteolysis from chloroplastic ATP synthase of herbivore-damaged plants (27,28); disulfo-oxy fatty acids of grasshopper regurgitant, named caeliferins (29); and the enzyme ␤-glucosidase from Pieris brassicae oral secretions (8). Application of these elicitors onto plant wounds results in the release of volatiles that repel ovipositing herbivores (30) or attract natural enemies of herbivores (31).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been demonstrated that specific Lepidopteran oral secretion elicitors can be used to predict elicitation of legume defense responses following natural bouts of herbivory (Schmelz et al 2006(Schmelz et al , 2012. First identified from beet armyworm S. exigua larvae, fatty acid-amino acid conjugates (FACs) remain the most extensively examined insect-produced elicitors (Alborn et al 1997).…”
Section: Introductionmentioning
confidence: 99%